2020
DOI: 10.21037/atm-20-996
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the burden of lung cancer attributable to tobacco exposure in China and the USA

Abstract: Background: Tobacco exposure (TE) is the major contributor to lung cancer mortality worldwide. This study aims to clarify the possible reasons underlying the long-term trends and differences in lung cancer mortality attributable to TE in China and the United States of America (USA).Methods: Lung cancer mortality data from China and the USA were obtained from the Global Burden of Disease (GBD) Study 2017. Joinpoint regression analysis was used to assess the magnitude and direction of trends from 1990 to 2017, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The relevant methods for mortality standardization in the GBD database have been introduced in previous studies [ 16 , 17 ]. To assess the magnitude and direction of trends in the mortality rate of lung cancer over time, we used JoinPoint software (Version 4.7.0.0) to calculate the average annual percentage change (AAPC) and the corresponding 95% CIs by joinpoint regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The relevant methods for mortality standardization in the GBD database have been introduced in previous studies [ 16 , 17 ]. To assess the magnitude and direction of trends in the mortality rate of lung cancer over time, we used JoinPoint software (Version 4.7.0.0) to calculate the average annual percentage change (AAPC) and the corresponding 95% CIs by joinpoint regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the smoking rate tended to plateau in 2002 (Yang et al 2005), and fell by 1.8% in 2015, which showed a slow decline compared with early 1996. Moreover, the mortality of lung cancer in this region was 22.89/100,000 in 2002, and increased to 36.03/100,000 in 2015(Global Health Data Exchange 2018Wu et al 2020). The mortality of lung cancer showed an increasing trend over the past decade, but the mortality of lung cancer in this region showed no declining trend at present.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, fostering smoke-free environments and providing readily accessible smoking cessation support services, such as counseling and nicotine replacement therapies, are crucial for facilitating smokers’ quitting efforts 20 , 30 . This multifaceted approach demands the collaborative involvement of government agencies, community organizations, and the wider public to foster a healthier living environment and reduce the risk of diseases such as IHD 28 , 31 . In our study, we also observed that the decline in mortality rates among men and the older age groups is slower, and there is a continuous increase in the DALYs rates among the elderly population in middle-income countries.…”
Section: Discussionmentioning
confidence: 99%